OPTIMAL and ENSURE trials-based combined cost-effectiveness analysis of erlotinib versus chemotherapy for the first-line treatment of Asian patients with non-squamous non-small-cell lung cancer. Issue 4 (13th April 2018) - Wen, Feng; Zheng, Hanrui; Zhang, Pengfei; Hutton, David; Li, Qiu
Abstract : Objectives: Erlotinib, the first generation of epidermoid growth factor receptor-tyrosine kinase inhibitor (EGFR-TKI), has been recommended as an essential treatment in patients with non-small-cell lung cancer (NSCLC) with EGFR mutation. Although it has improved progression-free survival (PFS), overall survival (OS) was limited and erlotinib can be expensive. This cost-effectiveness analysis compares erlotinib monotherapy with gemcitabine-included doublet chemotherapy. Setting: First-line treatment of Asian patients with NSCLC with EGFR mutation. Methods: A Markov model was created based on the results of the ENSURE (NCT01342965 ) and OPTIMAL (CTONG-0802) trials which evaluated erlotinib and chemotherapy. The model simulates cancer progression and all causes of death. All medical costs were calculated from the perspective of the Chinese healthcare system. Main outcome measures: The primary outcomes are costs, quality-adjusted life years (QALYs) and incremental cost-effectiveness ratios (ICERs). Results: The combined PFS was 11.81 months and 5.1 months for erlotinib and chemotherapy, respectively, while the OS was reversed at 24.68 months for erlotinib and 26.16 months for chemotherapy. The chemotherapy arm gained 0.13 QALYs compared with erlotinib monotherapy (1.17 QALYs vs 1.04 QALYs), while erlotinib had lower costs ($55 230 vs $77 669), resulting in an ICER of $174 808 per QALY for the chemotherapy arm, which exceeds three times the Chinese GDP per capita. The most influential factors were the health utility of PFS, the cost of erlotinib and the health utility of progressed disease. Conclusion: Erlotinib monotherapy may be acceptable as a cost-effective first-line treatment for NSCLC compared with gemcitabine-based chemotherapy. The results were robust to changes in assumptions. Trial registration number: NCT01342965 and CTONG-0802.